Biochemical and molecular characterization of PepR, a dipeptidase, from Lactobacillus helveticus CNRZ32. - Shao, W (1997)
A dipeptidase with prolinase activity from Lactobacillus helveticus CNRZ32, which was designated PepR, was purified to gel electrophoretic homogeneity and characterized. The NH2-terminal amino acid sequence of the purified protein had 96% identity to the deduced NH2-terminal amino acid sequence of the pepR gene, which was previously designated pepPN, from L. helveticus CNRZ32. The purified enzyme hydrolyzed Pro-Met, Thr-Leu, and Ser-Phe as well as dipeptides containing neutral, nonpolar amino acid residues at the amino terminus. Purified PepR was determined to have a molecular mass of 125 kDa with subunits of 33 kDa. The isoelectric point of the enzyme was determined to be 4.5. The optimal reaction conditions, as determined with Pro-Leu as substrate, were pH 6.0 to 6.5 and 45 to 50 degrees C. The purified PepR had a Km of 4.9 to 5.2 mM and a Vmax of 260 to 270 mumol of protein per min/mg at pH 6.5 and 37 degrees C. The activity of purified PepR was inhibited by Zn2+ but not by other cations or cysteine, serine, aspartic, or metal-containing protease inhibitors or reducing agents. Results obtained by site-directed mutagenesis indicated that PepR is a serine-dependent protease. Gene replacement was employed to construct a PepR-deficient derivative of CNRZ32. This mutant did not differ from the wild-type strain in its ability to acidify milk. However, the PepR-deficient construct was determined to have reduced dipeptidase activity compared to the wild-type strain with all dipeptide substrates examined.